2005
DOI: 10.2337/diabetes.54.5.1534
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Are Associated With Capillary Closure in Spontaneously Diabetic Monkey Retinas

Abstract: Type 2 diabetes develops spontaneously in obese aging rhesus monkeys (Macaca mulatta). This study investigates the association between polymorphonuclear leukocytes and development of retinopathy. Blood pressure and plasma glucose levels were determined in 15 diabetic and 6 nondiabetic monkeys. The plasma levels of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides were determined just before the start of the animal's final decline and elective necropsy. Retinas were incubated for ADPase (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 36 publications
1
64
1
2
Order By: Relevance
“…However, though well established in rodent models of DR, there is no direct clinical evidence that leukostasis is occurring in DR patients. Evidence for leukostasis leading to retinal capillary nonperfusion in the retinas of obese aging rhesis monkeys was obtained by Kim and co-workers [140]. Although the analysis was not blinded and included "selected regions of interest" rather than randomly-selected regions, these authors found increased numbers of esterase staining granulocytes in retinal capillaries of diabetic versus control monkeys.…”
Section: Little Is Known About Leukocyte Trafficking In the Retina Dumentioning
confidence: 93%
“…However, though well established in rodent models of DR, there is no direct clinical evidence that leukostasis is occurring in DR patients. Evidence for leukostasis leading to retinal capillary nonperfusion in the retinas of obese aging rhesis monkeys was obtained by Kim and co-workers [140]. Although the analysis was not blinded and included "selected regions of interest" rather than randomly-selected regions, these authors found increased numbers of esterase staining granulocytes in retinal capillaries of diabetic versus control monkeys.…”
Section: Little Is Known About Leukocyte Trafficking In the Retina Dumentioning
confidence: 93%
“…Other proinflammatory effects related to Grx1 S-glutathionylation have been reported. Neutrophils play a key role in inflammation processes, such as those related to diabetic nephropathy (Galkina and Ley, 2006), adipose tissue inflammation and diabetic retinopathy (Kim et al, 2005). Neutrophils from diabetic patients have decreased phagocytic activity, impaired bacterial killing and significantly more superoxide generation compared to control neutrophils.…”
Section: Diabetic Animal Models and S-glutathionylationmentioning
confidence: 99%
“…The firm adhesion of neutrophils to the endothelium is responsible for capillary closure and the development of diabetic angiopathies. 94,95 In the circulation, shear stress and a network of mediators, such as prostanoids and nitric oxide (NO) prevent firm leukocyte adhesion to the endothelium. 96 Both endothelial cells and neutrophils express constitutively active NO synthase isoforms, such as eNOS in endothelial cells and nNOS (neuronal) and iNOS (inducible) in neutrophils, for the production of NO.…”
Section: 83mentioning
confidence: 99%